The role of minimal access valve surgery in the elderly. A meta-analysis of observational studies. (September 2016) - Moscarelli, Marco; Emmanuel, Sam; Athanasiou, Thanos; Speziale, Giuseppe; Fattouch, Khalil; Casula, Roberto
Abstract: Background: Minimal access valve surgery, both mitral and aortic, may be related to improvement in specific post-operative outcomes, therefore may be beneficial for the subgroup of the elderly referred for valve surgery. Methods: A systematic literature review identified several different studies, of which 6 fulfilled criteria for meta-analysis. Outcomes for a total of 1347 patients (675 conventional standard sternotomy and 672 minimally invasive valve surgery) were assessed with a meta-analysis using random effects modeling. Heterogeneity, subgroup analysis with quality scoring were also assessed. The primary endpoint was early mortality. Secondary endpoints included intra and post-operative outcomes. Results: In the context of elderly patients, minimal access valve surgery conferred comparable early mortality to standard sternotomy (odd ratio (OR) 0.79, CI [0.40, 1.56], p = 0.50) with no heterogeneity (p = 0.13); it was also associated with reduced mechanical intubation time (OR 0.48, CI [0.30, 0.78], p = 0.003) and reduced post-operative length of stay (weighted mean difference (WMD) −2.91, CI [−3.09, −2.74] p < 0.00001), however both cardio-pulmonary bypass time and cross clamp time were longer (WMD 24.29, CI [22.97, 25.61] p < 0.00001 and WMD 8.61, CI [7.61, 9.61], p < 0.00001, respectively); subgroup analysis demonstrated statistically significant reduced post-operative length of stay for both minimally invasive aortic and mitral surgery (WMD −2.84, CI [−3.07, −2.60] p < 0.00001 and WMD −2.98, CI [−3.25, −2.71] p < 0.00001 respectively). Conclusions: Despite a prolonged cardiopulmonary bypass and cross clamp time, minimally invasive valve surgery is a safe alternative to standard sternotomy in the elderly, with similar early mortality, and improvements in intubation time as well as length of stay. Highlights: Minimal access valve surgery is a safe alternative to the sternotomy approach in elderly patients. The approach demonstrates reduced mechanical ventilation time and reduced length of stay. Mortality is comparable to those undergoing a conventional sternotomy. Limitations for this approach include prolonged cardiopulmonary bypass and cross-clamp time.